2018
DOI: 10.1029/2017jb015338
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Controls on Frictional Strength, Stability, and Shear Permeability Evolution of Fractures

Abstract: Massive fluid injection into the subsurface can induce microearthquakes by reactivating preexisting faults or fractures as seismic or aseismic slip. Such seismic or aseismic shear deformations may result in different modes of permeability evolution. Previous experimental studies have explored frictional stability-permeability relationships of carbonate-rich and phyllosilicate-rich samples under shear, suggesting that friction-permeability relationship may be primarily controlled by fracture minerals. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 55 publications
4
40
0
Order By: Relevance
“…Considering that the fracture permeabilities after the velocity step are mostly higher than those before the velocity step (Figure ), it is clear that fracture permeability is enhanced due to the velocity step. Such response in fracture permeability to the velocity step is preliminarily confirmed in Ishibashi, Asanuma, et al () and is consistent with the experimental observation in Fang et al (). Moreover, Im et al () has reported that permeability response switches from net reduction to net increase following fracture reactivation (i.e., upon reactivating an instantaneous slide following holding) that is consistent with the present study.…”
Section: Experimental Results and Analysissupporting
confidence: 88%
“…Considering that the fracture permeabilities after the velocity step are mostly higher than those before the velocity step (Figure ), it is clear that fracture permeability is enhanced due to the velocity step. Such response in fracture permeability to the velocity step is preliminarily confirmed in Ishibashi, Asanuma, et al () and is consistent with the experimental observation in Fang et al (). Moreover, Im et al () has reported that permeability response switches from net reduction to net increase following fracture reactivation (i.e., upon reactivating an instantaneous slide following holding) that is consistent with the present study.…”
Section: Experimental Results and Analysissupporting
confidence: 88%
“…Permeability might decrease thank to shear-enhanced compaction (Crawford et al, 2008), swelling of clays (Cuss et al, 2011;Fang et al, 2017Fang et al, , 2018, and clay-fabric development (Ikari et al, 2009). Permeability might decrease thank to shear-enhanced compaction (Crawford et al, 2008), swelling of clays (Cuss et al, 2011;Fang et al, 2017Fang et al, , 2018, and clay-fabric development (Ikari et al, 2009).…”
mentioning
confidence: 99%
“…Laboratory tests have shown that once fault slip on preexisting faults in shales occurs, fault permeability can be either depleted or enhanced. Permeability might decrease thank to shear-enhanced compaction (Crawford et al, 2008), swelling of clays (Cuss et al, 2011;Fang et al, 2017Fang et al, , 2018, and clay-fabric development (Ikari et al, 2009). Conversely, permeability might increase due to deformation-induced dilatancy when sheared at low to moderate effective stresses (Im et al, 2018;Lefèvre et al, 2016;Wu et al, 2017;Zhang & Cox, 2000).…”
mentioning
confidence: 99%
“…Permeability, k (m 2 ), was evaluated assuming the cubic law of a single fracture (Witherspoon et al, ; Fang, Elsworth, Wang, et al, ; Ishibashi et al, ), and using the measured fluid flow rate for a given pressure differential: b=12μ·L()t·Q()tW·P130.25em k=b2120.25em …”
Section: Experimental Methodsmentioning
confidence: 99%
“…Velocity strengthening behavior results in aseismic (stable) slip while velocity-weakening behavior is a necessary condition for seismic (unstable) slip. In general, experimental observations have shown that frictional strength and stability follow a reverse relationship: when strength is high, stability is low, as summarized in Fang, Elsworth, Wang, et al (2018). Microphysical models have shown that this results from the mechanics of surface contact and microstructure deformation of individual crystalline phases (Niemeijer & Collettini, 2013;Niemeijer & Spiers, 2007).…”
Section: 1029/2019jb017805mentioning
confidence: 99%